Synergistic Effect of Cinnamon Oil and Butyric Acid onGrowth Performance, Oxidative Stress, Immunological andIntestinal Histomorphology of Broiler Chickens - Doneria, Raina; Dubey, Meenu; Gendley, Manoj Kumar; Pathak, Rupal; Nety, Shraddha; Parmar, Mehtab Singh (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present experiment evaluated the effect of cinnamon oil (CEO) and butyric acid (BA) on the performance, oxidative stress parameters,  immune response and intestinal histomorphology of broiler chickens. Day-old broiler chicks (n=150) were distributed randomly into  five experimental groups. The experimental groups were control: T0 (basal diet without bacitracin), T1 (basal diet + bacitracin @ 50 mg/ kg diet), T2 (basal diet + 400 mg/kg CEO), T3 (basal diet + 0.4 % BA), T4 (basal diet + 400 mg/kg CEO + 0.4% BA). Our results revealed  that feed intake was significantly lower in T4, though a significant escalation in overall weight gain, and feed conversion ratio (FCR) was  observed. Furthermore, T4 group exhibited a significantly higher defeathered, eviscerated, dressed weight and increased glutathione  concentration as compared to T0. The haemagglutination inhibition (HI) titer against Newcastle Disease Virus (NCDV) was significantly  higher in all the treatment groups as compared to T0. Additionally, significantly (p
Keywords: Broiler; acid; Cinnamon oil; Growth performance; Immune response; Oxidative stress